Development and validation of an HPLC/UV method for quantification of bioactive peptides in fermented milks - Isabel M P L V O Ferreira (2007)
The simultaneous separation and quantification of two casein peptides (IPP, VPP) presenting potent inhibitory activity of angiotensin-converting-enzyme (ACE) and casein in fermented milks was developed. Gradient elution was carried out at a flow-rate of 1 mL/min, using a mixture of two solvents. Solvent A was 0.1% TFA in water and solvent B was acetonitrile-water-trifluoracetic acid 95:5:0.1. The effluent was monitored by UV detector at 214 nm. Calibration curves were constructed in the interval of 0.01-1.0 mg/mL for VPP, 0.005-1.0 mg/mL for IPP, and 0.05-3.0 mg/mL for casein. R 2 invariably exceeded 0.999. The detection limits were 0.004 for VPP, 0.002 mg/mL for IPP, and 0.02 mg/mL for casein. Repeatability of the method was evaluated by six consecutive injections of two standard solutions containing VPP, IPP, and casein. The RSD values for concentration were all below 5.08%. Recovery studies were carried out to determine the accuracy of the method. Recoveries ranged between 88 and 98.2%. The methodology was applied, not only, for the monitorization of VPP, IPP, and casein in commercial fermented milks labeled as presenting anti hypertensive properties, but also, in milk with different degrees of fermentation by L Helveticus, and in other commercial functional fermented milks, such as, those presenting cholesterol lowering properties.